2022
DOI: 10.3389/fendo.2022.905703
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 upregulation under high glucose induces podocyte apoptosis and impairs β-cell insulin secretion

Abstract: ObjectivesThe progressive impairment of β-cell function results in prolonged deterioration in patients with type 2 diabetes mellitus (T2DM). Interestingly, the finding on pancreatitis secondary to renal injury suggests that potential communication exists between kidney and pancreas. Therefore, we aimed to investigate cell division cycle 42 (Cdc42)-mediated podocyte apoptosis and its effect on insulin secretion in islet β-cells.MethodsType 2 diabetic nephropathy mouse models were established to identify the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(39 reference statements)
3
5
0
Order By: Relevance
“…This finding was partly in line with a previous study, which discovers that CDC42 is upregulated under HG in human renal (Li et al 2020). The reason behind this might be that HG could induce cytoskeletal reorganization; meanwhile, CDC42 was a key regulatory of cytoskeletal reorganization, which could reflect the cytoskeletal changes (Jiang et al 2022). Therefore, an increase in CDC42 was observed under the HG condition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding was partly in line with a previous study, which discovers that CDC42 is upregulated under HG in human renal (Li et al 2020). The reason behind this might be that HG could induce cytoskeletal reorganization; meanwhile, CDC42 was a key regulatory of cytoskeletal reorganization, which could reflect the cytoskeletal changes (Jiang et al 2022). Therefore, an increase in CDC42 was observed under the HG condition.…”
Section: Discussionsupporting
confidence: 91%
“…Cell division control protein 42 (CDC42) is a member of the Rho GTPases family, which has been found to participate in the modulation of diabetic complications and retinal vascular diseases (Huang et al 2019, Uemura andFukushima 2021). According to a study, CDC42 is upregulated under high glucose (HG), which further causes podocyte apoptosis and attenuates β-cell insulin secretion in type 2 diabetic nephropathy mice (Jiang et al 2022). In addition, another study reports that HGinduced CDC42 participates in the change of the number and length of filopodia in podocytes, which is responsible for the pathology of diabetic nephropathy (Shen et (Lavina et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…CDC42 promotes proliferation and migration of cancer cells under high glucose conditions, activates JNK to produce inflammatory factors and affects insulin signaling through the CDC42-MKK4 pathway. [26][27][28] RAC1 is a membrane GTPase that determines the intensity of oxidative stress. RAC1 in a high glucose state can over-activate NADPH oxidase, which in turn causes cellular oxidative stress damage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have indicated that CDC42 participates in the incidence and progression of DN ( 17 , 18 ). For example, in a mouse model with DM decreased expression levels and activity of CDC42 leads to podocyte apoptosis and proteinuria ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a mouse model with DM decreased expression levels and activity of CDC42 leads to podocyte apoptosis and proteinuria ( 17 ). Another study reported that CDC42 reduction under high glucose inhibits podocyte apoptosis and affects β-cell insulin secretion in a type 2 DM-induced DN mouse model ( 18 ). However, the clinical role of CDC42 for estimating the development and progression of DN in patients with DM is currently unknown.…”
Section: Introductionmentioning
confidence: 99%